The Role Of Physical And Social Teacher As A Media In Character Education Of State Elementary School Students In Montong Gading District - Sekar, Sekar Pudak Wangi; Susi, Susi Yundarwati; Trisnar Adi Prabowo (Journal Sport Science Indonesia, 2025)
The gap in character cultivation of students at school can be seen from the deviant behaviors often exhibited by the students, both during the teaching and learning process and outside of school hours. The mentioned deviant behaviors include indiscipline in participating in learning activities, a lack of empathy towards teachers and peers, undiscipline in dressing, littering, not retrurning items to their original places, and frequently using foul language. This research aims to gain an understanding and wants to know about the role of PJOK teachers as a medium in the character education of elementary school students in Montong Gading sub-district. This type of research is descriptive quantitative with a survey method. This research instrument used is a questionnaire. The sampling technique used is saturation sampling, wich involves the entire population of 28 PJOK teachers as respondents. Data analysis techniques using desriptive statistics quantitatively. The results show that the role of PJOK teachers serves as media in character education for elementary school students in Montong Gading sub-district, categorized into sveral groups, is dominated by the “adeuate” category with peresentage of 42,86%. Other categories include “verry good” at 7,14%, “good” category at 21,43%, “lacking” catagory at 17,8%, and 10,71% in the “very lacking” category. Further research is expected to cover a wider area with a larger number of respondents, multiple levels of education, and a mixed methods approach in order to obtain a more comprehensive picture of the role of Physical Education teachers in character education.